Measuring Tax Compliance Levels Of Taxpayer: Sample Of The Mediterranean Region - Tekin, Ahmet (Fırat Üniversitesi, 2023)
In this study, it is aimed to examine the tax compliance levels of taxpayers in Adana, Antalya, Burdur, Hatay, Isparta, Kahramanmaraş, Mersin and Osmaniye provinces in the Mediterranean Region. The main reason why the study was conducted in the Mediterranean Region is that no study on the Mediterranean Region has been encountered before. When the previous studies were examined, it was observed that studies were generally conducted on taxpayers located in a single city. Face-to-face survey method was used in the study. While applying the questionnaire, it was taken on a voluntary basis and it was stated that the answers given by the participants would not be shared with any institutions or organizations. 1013 taxpayers participated in the study and the answers given by the taxpayers were analyzed with the SPSS package program. The vast majority of respondents to the survey are men. Majority of the respondents are undergraduate graduates. In addition, the vast majority of respondents are commercial earners. In addition, the participants defend the view that "higher income tax should be collected from those with high income and lower income tax from those with low income". “Tax legislation is unfair.” Most of the participants stated that they strongly agree with the question. “I find tax rates high.” Most of the participants stated that they absolutely agree with the question. The study also shows the feature of being a first because it covers 8 provinces in the Mediterranean Region.

Bu çalışmada Akdeniz Bölgesinde yer alan Adana, Antalya, Burdur, Hatay, Isparta, Kahramanmaraş, Mersin ve Osmaniye illerinde bulunan mükelleflerin vergi uyum düzeylerinin incelenmesi amaçlanmıştır. Çalışmanın Akdeniz Bölgesi’nde yapılmasının temel sebebi ise daha önce Akdeniz Bölgesi üzerine herhangi bir çalışmaya rastlanılmamış olmasıdır. Daha önce yapılmış çalışmalar incelendiğinde genellikle tek bir şehirde bulunan mükellefler üzerine çalışmalar yapıldığı gözlenmiştir. Çalışmada yüz yüze anket yöntemi uygulanmıştır. Anket uygulanırken gönüllülük esası alınmış ve katılımcılara verdikleri cevapların hiçbir şekilde kurum ya da kuruluşlarla paylaşılmayacağı belirtilmiştir. Çalışmaya 1013 mükellef katılmış ve mükelleflerin vermiş oldukları cevaplar SPSS paket programı ile analiz edilmiştir. Ankete cevap veren katılımcıların büyük bir çoğunluğu erkeklerden oluşmaktadır. Ankete katılanların çoğunluğu lisans mezunudur. Ayrıca ankete katılanların büyük bir çoğunluğu ticari kazanç elde edenlerdir. Ayrıca katılımcılar “kazancı yüksek olanlardan daha yüksek, düşük olanlardan daha düşük oranda gelir vergisi alınmalı” görüşünü savunmaktadırlar. “Vergi mevzuatı adil değildir.” sorusuna katılımcıların çoğu kesinlikle katıldıklarını belirtmiştir. “Vergi oranlarını yüksek bulurum.” sorusuna katılımcıların çoğu kesinlikle katıldığını belirtmiştir. Çalışma Akdeniz Bölgesinde yer alan 8 ili kapsaması nedeniyle bir ilk olma özelliğini de göstermektedir.
MÜKELLEFLERİN VERGİ UYUM DÜZEYLERİNİN ÖLÇÜLMESİ: AKDENİZ BÖLGESİ ÖRNEĞİ